Dampak Geopolitik Perang Israel-Iran Terhadap Pengelolaan Portofolio Investasi Global - Romadhon, Moch Iqbal; Amalia, Devina Shava; Fauziyah, Ataina Rusyda; Pandin, Maria Yovita R (Innovative: Journal Of Social Science Research, 2024)
The long-running war between Israel and Iran creates economic and political uncertainty, which can impact international financial markets, commodity prices and investment flows. To compare their results, we use the meta-analysis method in this article. The available data shows that the Israel-Iran conflict affects global portfolio investment management.